2014
DOI: 10.1542/peds.2014-1974
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association Between Teen Sexting and Sexual Behavior

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Cross-sectional research indicates that teen sexting is common, may be associated with other adolescent behaviors such as substance use, does not appear to be a marker of mental well being, and is probably an indicator of actual sexual behaviors. WHAT THIS STUDY ADDS:Although mounting evidence links teen sexting to sexual behavior, little is known about the temporal sequencing of these 2 behaviors. Knowing which comes first will aid tween-and teen-focused health care providers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
3
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(150 citation statements)
references
References 19 publications
8
130
3
9
Order By: Relevance
“…It is estimated that ∼12% of youth aged 10 to 19 years have ever sent a sexual photo to someone else. 44 The Internet also has created opportunities for the exploitation of children by sex offenders through social networking, chat rooms, e-mail, and online games. 45 …”
Section: Media Infl Uencementioning
confidence: 99%
“…It is estimated that ∼12% of youth aged 10 to 19 years have ever sent a sexual photo to someone else. 44 The Internet also has created opportunities for the exploitation of children by sex offenders through social networking, chat rooms, e-mail, and online games. 45 …”
Section: Media Infl Uencementioning
confidence: 99%
“…Because of the more distant and asynchronic nature of digital communication, it might make some users more comfortable to express their emotions and sexual desires though digital sexually explicit messages, as opposed to in-person contact (Van Ouytsel et al 2017). Research has also found that sexting among adolescents could function as a first step towards sexual activity, as it has been found to precede and co-occur with offline forms of sexual contact (Kosenko et al 2017;Temple and Choi 2014). Longitudinal research has shown that sexting is significantly more likely to precede offline sexual activity, but not sexual risk behavior, among adolescents.…”
Section: Motivesmentioning
confidence: 99%
“…Longitudinal research has shown that sexting is significantly more likely to precede offline sexual activity, but not sexual risk behavior, among adolescents. Some adolescents could use sexting to indicate their willingness to engage in offline sexual behavior or they could use it to indicate their readiness to take the relationship further (Temple and Choi 2014). Among adults, sexting has also been found as way to engage in sexual hook-ups (Dir et al 2013).…”
Section: Motivesmentioning
confidence: 99%
“…Youth who are sexters are more sexually active (Dake et al, 2012;Dir et al, 2013;Houck, Barker, Rizzo, Hancock, Norton, & Brown, 2014;Rice et al, 2014;Sorbring et al, 2014) and became sexually active earlier in life (Englander, 2012;Rice et al, 2014;Perkins et al, 2014). In a recent six-year longitudinal study (Temple & Choi, 2014), data were used from wave 2 (spring 2011) and 3 (spring 2012). Participants included 964 adolescents with a mean age of 16.…”
Section: Associations With Sexual Behavioursmentioning
confidence: 99%
“…However, research shows that sexual communication in text or through pictures or films is often seen as part of dating behaviour (e.g. Temple & Choi, 2014). In a recent Swedish study (Sorbring et al, 2014), online and offline sexual and romantic activities were investigated in relation to wellbeing.…”
Section: Online Dating For Romantic or Sexual Relationshipsmentioning
confidence: 99%